Framing Analysis of Drought News in Java at detik.com - Susilo, Daniel; Harliantara, Harliantara (Innovative: Journal Of Social Science Research, 2023)
This study examines the manner in which sustainability issues are portrayed in Indonesian media during persistent drought conditions, specifically exploring how these portrayals may exonerate the government from accountability for its dedication to sustainable development. The research is based on the concept that the framing of news has a significant impact on the formation of public opinions and the discussion of policies. A framing analysis was performed on a specific set of news articles sourced from Detik.com, a prominent media station in Indonesia. The primary objective of the analysis was to determine the prevailing frameworks utilised in the representation of sustainability challenges and drought, together with its consequences in assigning blame for these problems. The findings indicate a dearth of ethical assessment within news framing, thereby serving as a protective barrier for the government against scrutiny about its commitment to sustainable development. In spite of the frequent occurrence of droughts and the increasing issues related to sustainability, media coverage frequently neglects to thoroughly analyse or critically examine the steps taken by the state. In contrast, news narratives often have a tendency to provide fatalistic depictions of environmental challenges or attribute responsibility to external sources, such as climate change or global economic situations. This study highlights the necessity for increased critical and evaluative journalism pertaining to sustainability matters in Indonesia. By shedding light on the ways in which present framing practises might lead to a shirking of political accountability, it emphasises the need for increased journalistic examination of state obligations pertaining to sustainable development. Furthermore, this emphasises the potential impact of media coverage that is both balanced and accountable in promoting greater social involvement in addressing sustainability issues.